Copper-catalyzed synthesis and applications of yndiamides - Anderson, E; Mansfield, S; Christensen, K; Thompson, A; Ma, K; Jones, M; Mekareeya, A (Wiley, 2017)
The first synthetic route to yndiamides, a novel class of double aza-substituted alkyne, has been established via copper (I)-catalyzed cross-coupling of 1,1-dibromoenamides with nitrogen nucleophiles. The utility of these compounds is demonstrated in a range of transition metal- and acid-catalyzed transformations, which afford a wide variety of 1,2-diamide functionalized products.